Case Report: Immune Microenvironment and Mutation Features in a Patient With Epstein–Barr Virus Positive Large B-Cell Lymphoma Secondary to Angioimmunoblastic T-Cell Lymphoma - Zhang, Fen; Li, Wenyu; Cui, Qian; Chen, Yu; Liu, Yanhui (Frontiers in Genetics, 2022)
On rare occasions, secondary Epstein–Barr virus (EBV)-associated B cell lymphoma can develop from patients with angioimmunoblastic T-cell lymphoma (AITL). Here, we described the tumor microenvironment (TME) and mutation features of a patient with EBV+ large B-cell lymphoma (LBCL) secondary to AITL. He admitted to hospital due to one-year history of fever and the enlarged right inguinal lymph nodes. A biopsy of the right inguinal lymph node demonstrated numerous diffuse medium-sized atypical lymphocytes proliferated, together with increased extrafollicular follicular dendritic cell meshwork, and the lymphocytes expressed CD3, CD4, BCL6, CD10, PD-1, CXCL13 and Ki-67 (75%). Thus, a diagnosis of AITL was made. However, the disease was progressed following the treatment of CHOP regimen (cyclophosphamide, adriamycin, vincristine, and prednisone). Biopsy showed most of the cells were positive for CD20 staining and IgH rearrangement. Analysis of 22 kinds of immune cells showed that the numbers of activated NK cells and activated memory T cells were increased, while T-follicular helper population was decreased in the transformed sample. Also, compared with the primary sample, RHOA (G17V) mutation was not detected, while JAK2 and TRIP12 gene mutations were detected in the transformed sample. Overall, we described the immune microenvironment and mutation features of a patient with EBV+ LBCL secondary to AITL. This study will help us to understand the mechanisms by which AITL transforms to B-cell lymphoma.